A geostatistical methodology to simulate the transmissivity in a highly heterogeneous rock body based on borehole data and pumping tests - Barbosa, Sofia (2022)
A geostatistical methodology is developed with the aim of simulating three-dimensional grids of transmissivity. The case study is a highly heterogeneous massif rock body, mainly composed of granites and schists with distinct weathering and fracture conditions, that surrounds and is part of a former uranium mine in central Portugal. Contrasting hydraulic behaviour is given by fractured rock and a pervasively weathered rock matrix composed mainly by clay minerals. Lithology, weathering, and fracture were the geological attributes selected for simulation. Data and information were analysed in detail for their respective integration into a sequential geostatistical modelling approach. The simulation process was conditioned to local data histograms. Simulation images of transmissivity show high degrees of heterogeneity both laterally and vertically. Potential areas for high-flow propagation are restricted in number and interconnectivity is not particularly evident. Small channels, the main structures responsible for groundwater flow propagation, can be identified within the rock body.